Studies on the Topography of Reovirus and Bluetongue Virus Capsid Proteins - Martin, Scott A. (1973)
Protein labeling experiments confirm the surface location of proteins 2 and 5 in bluetongue virus, and proteins σ3 and μ2 in reovirus. Lambda 2 is the major surface component of the reovirus core, and proteins 1, 3, and 4 appear to be the outer components of the bluetongue virus subviral particle.